2018
DOI: 10.1002/aenm.201703295
|View full text |Cite
|
Sign up to set email alerts
|

Device Characteristics of an 11.4% CZTSe Solar Cell Fabricated from Sputtered Precursors

Abstract: Kesterite is an attractive material for absorber layers in thin film photovoltaics. Solar cells based on kesterite have shown a substantial progress over the last decade; nevertheless, further improvements in device efficiency are pending due to the open‐circuit voltage (Voc) deficit (i.e., difference between the maximum V oc that can be achieved according to Shockley–Queisser limit and actual V oc from the device). In this study, the optoelectronic properties of the author's internal record Cu2ZnSnSe4 solar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
68
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 33 publications
4
68
0
1
Order By: Relevance
“…This champion sputtering‐based solar cell was fabricated in a different batch, using the optimized baseline process, achieving an efficiency greater than 11%, and is shown for comparison. As can be seen, relatively high current densities are achieved, exceeding 39 mA/cm 2 , which are at the same level of the best cells reported so far for the pure selenide CZTSe compound . Nonetheless, V OC and especially FF values remain still lower compared with these record devices.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…This champion sputtering‐based solar cell was fabricated in a different batch, using the optimized baseline process, achieving an efficiency greater than 11%, and is shown for comparison. As can be seen, relatively high current densities are achieved, exceeding 39 mA/cm 2 , which are at the same level of the best cells reported so far for the pure selenide CZTSe compound . Nonetheless, V OC and especially FF values remain still lower compared with these record devices.…”
Section: Resultssupporting
confidence: 70%
“…Currently, the certified highest efficiency (12.6%) has been achieved using hydrazine‐based solution approach, although the wide variety of deposition techniques, like coevaporation, sputtering, spray, spin‐coating, or doctor‐blade coating, have also given efficiencies above 10%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth to mention that there could be secondary phases underneath the surface, which is very likely at this composition range. Our previous work showed that a small quantity of ZnSe secondary phase exists at the back side of the absorber …”
Section: Resultsmentioning
confidence: 99%
“…In this report, we present our results from an easy to adapt two‐stage approach for fabrication of kesterite thin film absorbers, which contains the vacuum deposition of a metallic precursor layer followed by an annealing step under chalcogen vapor at high temperatures. The process leads to device efficiencies above 11% . We focus on the annealing process and demonstrate the impact of the reactor pressure during selenization and the resulting final composition of CZTSe absorbers.…”
Section: Introductionmentioning
confidence: 99%